Evaluation of Early Submaximal Exercise Tolerance in Adolescents with Symptomatic Sport-related Concussion - Morissette, Marc P; Cordingley, Dean M; Ellis, Michael J; Leiter, Jeff R S (Medicine and science in sports and exercise, 2020)
This study aimed to compare cardiorespiratory response to a graded aerobic exercise challenge between adolescents with symptomatic sport-related concussion (SSRC) and healthy control subjects. A quasiexperimental nonrandomized study at a multidisciplinary pediatric concussion program was conducted. Thirty-four adolescents with SSRC (19 males and 15 females) and 40 healthy control subjects (13 males and 27 females) completed the Buffalo Concussion Treadmill Testing (BCTT) until either symptom exacerbation or volitional fatigue. Main outcome measures included heart rate (HR), oxygen consumption (V˙O2), carbon dioxide production (V˙CO2), and minute ventilation (V˙E) at rest and at test termination, and change from rest in variables (ΔHR, ΔV˙O2, ΔV˙CO2, and ΔV˙E) during the first five stages of the BCTT. Main outcomes were analyzed using three-way mixed-model ANOVA, with group status (control vs SSRC) and sex (male vs female) as between-subject factors, and time (BCTT stage) as the within-subject factor. No group differences in resting HR, systolic and diastolic blood pressure, ΔV˙O2, V˙CO2, and V˙E were observed. During the first five stages of the BCTT, no group differences in ΔV˙O2, V˙CO2, and V˙E were observed; however, SSRC patients demonstrated higher RPE (P < 0.0005) compared with control subjects. No sex-based differences were observed among SSRC patients on measures collected at rest and during early stages of BCTT. Although SSRC patients exhibited higher RPE during a graded aerobic exercise challenge, no differences in cardiorespiratory response were observed compared with control subjects exercising at equivalent workloads. Further work is needed to elucidate the physiological mechanisms underlying exercise intolerance after SSRC.